2020
DOI: 10.3390/socsci9030025
|View full text |Cite
|
Sign up to set email alerts
|

Culinary Tourism as An Effective Strategy for a Profitable Cooperation between Agriculture and Tourism

Abstract: The relationships between tourism and agriculture have traditionally been studied due to the positive impacts they can potentially have on the development of rural economies. This research puts forward a new interpretation of the cooperation between these two sectors, involving culinary tourism as a key factor. An empirical study was carried out and 720 tourists were interviewed while visiting the city of Cáceres, Extremadura, in south-western Spain. Results show that (i) food and traditional gastronomy are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Nevertheless, with the changing socio-economic landscape and the development of new types of markets, the agricultural unit of the Taiwan government has provided interventions by scholars and guidance organizations to guide the management of local farmers' organizations, promote the transformation of rural local organizations, and provide diverse development. For example, research by Jiménez-Beltrán et al [12], Rinaldi [13], Chaichana et al [25], and Di-Clemente et al [22] demonstrated that the processing of raw agricultural foods into products with commodity value and the transformation of production-oriented farms into sightseeing-oriented leisure farms, among other strategies, could attract foreign consumers, bolstering the rural local economy and creating rural innovation development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, with the changing socio-economic landscape and the development of new types of markets, the agricultural unit of the Taiwan government has provided interventions by scholars and guidance organizations to guide the management of local farmers' organizations, promote the transformation of rural local organizations, and provide diverse development. For example, research by Jiménez-Beltrán et al [12], Rinaldi [13], Chaichana et al [25], and Di-Clemente et al [22] demonstrated that the processing of raw agricultural foods into products with commodity value and the transformation of production-oriented farms into sightseeing-oriented leisure farms, among other strategies, could attract foreign consumers, bolstering the rural local economy and creating rural innovation development.…”
Section: Discussionmentioning
confidence: 99%
“…Delicacies and the enjoyment of delicious food are also important factors for local brand promotion [20,21]. Research on agriculture and tourism by Di-Clemente et al [22] revealed that food and traditional cooking are the main driving forces of modern tourists. Kim, Eves, and Scarles [23] considered local food tasting to be an opportunity for consumers to meet and communicate with family and friends, thereby building personal relationships or strengthening family connections.…”
Section: Introductionmentioning
confidence: 99%
“…Cimande Village plantation products including Slebor snakefruit and aloe vera, will be very interesting if developed into various attractions such as educational tours and tourist activities. Developing a variety of local-based specialties will be an effective strategy for rural tourism (Di-Clemente et al, 2020;Soeswoyo et al, 2021).…”
Section: S-o Strategymentioning
confidence: 99%
“…Food has always been an integral part of the tourism experience. For some tourists, food could even become the primary motivation to visit a destination [1,2] and to relish the culinary experience [3]. The culinary tourism phenomenon generates many socio-economic benefits, and one of them is to open opportunities for street food vendors to strengthen, enrich and differentiate what a destination could offer [4].…”
Section: Introductionmentioning
confidence: 99%